Kommunikation handel geld und banken in der fruhen neuzeit. - Michael North (Enzyklopädie deutscher Geschichte., 2014)
Michael North examines the common structural elements among the only seemingly heterogeneous areas of communication, trade, money, and banks. He demonstrates their specifically pan-European quality, as global influence was never more evident in any sector of the "German" economy than in these four areas. The latest research findings and an updated bibliography enhance the new edition.